A new era in treatment of cardiac amyloidosis: an overview of the Congress of cardiology - I. E. Strelkova (Лечащий Врач)
Amyloidosis is a group of diseases characterized  by accumulation of a protein of a specific fibrillar structure in the interstitium of various organs and tissues. The concept of amyloidosis  unites more than 30 different pathophysiological conditions,  each of which is based on abnormal synthesis of 30 different precursor proteins. However, 95% of amyloid cardiomyopathies are associated with just two proteins: a protein derived from light chains of immunoglobulins and a protein called transthyretin.  Determination of the precursor protein is a cornerstone of management  of patients with amyloid cardiomyopathy. Transthyretin  is a carrier protein of thyroxine, retinol and other substances, that performs vital functions. For hereditary or age-related reasons, TTR misfolding occurs in the liver. The resulting monomers, entering blood, form toxic intermediate products and amyloid fibrils. Cardiac amyloidosis (or amyloid cardiomyopathy)  used to be considered a rare disease. In the recent past, possibilities of therapy for cardiac amyloidosis were limited by prescription of diuretics, mineralocorticoid receptor antagonists and anticoagulants, since other drugs are not tolerated well by patients or are tolerated in minimal doses. Advent of the first drug specific for treatment of transthyretin amyloid cardiomyopathy in Russia increased a need of awareness of ATTR-CM among general practitioners  and cardiologists, and introduction of modern diagnostic algorithms for this disease. Timely detection and competent differential diagnosis of ATTR-CM from other types of amyloid cardiomyopathy  can play a decisive role in the prognosis of this disease. Tafamidis is a treatment that was shown to reduce mortality and CV-related hospitalization in ATTR-CM patients.